2014
DOI: 10.1016/j.measurement.2013.08.037
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the handheld adapter approach for measuring hand-transmitted vibration exposure

Abstract: The use of a handheld adapter equipped with a tri-axial accelerometer is the most convenient and efficient approach for measuring vibration exposure at the hand-tool interface, especially when the adapter is incorporated into a miniature handheld or wrist-strapped dosimeter. To help optimize the adapter approach, the specific aims of this study are to identify and understand the major sources and mechanisms of measurement errors and uncertainties associated with using these adapters, and to explore their impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 21 publications
2
14
1
Order By: Relevance
“…Material 3 showed less variation compared to Material 2, but more than Material 1. The resonance occurred around In comparison, previous studies using the palm adapter approach indicated that there were very small attenuation frequencies below 200 Hz (Griffin, 1998;Boyle and Griffin, 2001;Xu et al, 2014). While the design of the gloves (Welcome et al, 2014) and the structure and mechanical properties of glove material (Almagirby et al, 2015) affect results somewhat, the findings from the new test rig are consistent with previous findings.…”
Section: Transmissibility Measurementssupporting
confidence: 86%
See 1 more Smart Citation
“…Material 3 showed less variation compared to Material 2, but more than Material 1. The resonance occurred around In comparison, previous studies using the palm adapter approach indicated that there were very small attenuation frequencies below 200 Hz (Griffin, 1998;Boyle and Griffin, 2001;Xu et al, 2014). While the design of the gloves (Welcome et al, 2014) and the structure and mechanical properties of glove material (Almagirby et al, 2015) affect results somewhat, the findings from the new test rig are consistent with previous findings.…”
Section: Transmissibility Measurementssupporting
confidence: 86%
“…Many types of hand-held vibrating tools, such as chain saws, grinders, drills, and chipping hammers are widely used in several industries. Extended exposure to vibration transmitted from such tools may cause hand-arm vibration syndrome (HAVS) (Griffin, 1990;Xu et al, 2014). The National Institute for Occupational Safety and Health indicated that exposure to hand-transmitted vibration was also reported as being a major component associated with wrist syndrome (NIOSH, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The adapter approach seems a practical, convenient, and efficient choice for such measurement. A study has identified the basic requirements for the appropriate application of the adapter approach (Xu et al, 2014). However, it is unclear how this approach can be appropriately applied to measure the vibrations of the club heads during grinding and polishing processes.…”
Section: Methodsmentioning
confidence: 99%
“…Whenever necessary, the typical relationship between the BC and BD systems for each tool operation condition can be measured, and the experimental data measured in the BC system can be mathematically transformed into the BD system for analyzing biodynamic responses. A study has implemented this strategy [48] .…”
Section: General Principles and Practicesmentioning
confidence: 99%
“…The adapter may also be wrapped around the handle using an elastic material, to increase its stability and avoid dropping it during the tool operation. However, the hand-held adapter method, especially the fingers-held adapter method, is usually the least reliable among the four methods recommended for accelerometer installation [29] , [48] , [49] , [50] . The most reliable installation method is to install the accelerometer using a handle adapter firmly clamped on the handle, as shown in Fig.…”
Section: Bc Coordinate Systemmentioning
confidence: 99%